2015
DOI: 10.1016/j.abb.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Correlative microscopy

Abstract: In recent years correlative microscopy, combining the power and advantages of different imaging system, e.g., light, electrons, X-ray, NMR, etc., has become an important tool for biomedical research. Among all the possible combinations of techniques, light and electron microscopy, have made an especially big step forward and are being implemented in more and more research labs. Electron microscopy profits from the high spatial resolution, the direct recognition of the cellular ultrastructure and identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 126 publications
0
42
0
Order By: Relevance
“…It is widely recognized that the replacement of water with resin, during sample processing for electron microscopy, induces cell deformations. Therefore, a perfect superimposition of confocal and electron microscopy images is simply not attainable (Loussert Fonta and Humbel, 2015). Furthermore, because our protocol required epon resin, inclusion of fiduciary landmarks to help alignment was not feasible.…”
Section: Vrnps Outcompete Fips For Binding To Rab11a During Iav Infecmentioning
confidence: 99%
“…It is widely recognized that the replacement of water with resin, during sample processing for electron microscopy, induces cell deformations. Therefore, a perfect superimposition of confocal and electron microscopy images is simply not attainable (Loussert Fonta and Humbel, 2015). Furthermore, because our protocol required epon resin, inclusion of fiduciary landmarks to help alignment was not feasible.…”
Section: Vrnps Outcompete Fips For Binding To Rab11a During Iav Infecmentioning
confidence: 99%
“…Fluorescence microscopy aids to identify biomolecules2345, but lacks structural context. Correlated light microscopy and EM (CLEM)67 allows fluorescence-guided analysis of EM data, but fluorescence retention during EM sample preparation and overlay of images differing order-of-magnitude in resolution may be technically challenging67. In search for a broadly implementable technique to define molecules, organelles and cells at high resolution within mammalian tissue, we decided to implement element-guided identification using energy dispersive X-ray analysis (EDX).…”
mentioning
confidence: 99%
“…It has been reported that RV can become systemic leaving the intestinal route and emerging into the blood [24,25]. As the strain EDIM cannot be propagated in vitro [26], the viral load in the sera of pups was analyzed using a RV specific quantitative real-time polymerase chain reaction (RT-qPCR).…”
Section: Resultsmentioning
confidence: 99%